Emergency Operation Technologies for Sudden Water Pollution Accidents in the Middle Route of South-to-North Water Diversion Project - Lei, Xiaohui (IntechOpen, 2018)
The Middle Route of the South-to-North Water Diversion Project (MRP) is strategically important for China, and has made a great contribution to the sustainable development of society and economy in North China. Various potential risks of sudden water pollution accidents are distributed along the long canal, which may result in huge losses and endanger the safety of water supply. In order to provide technical support for emergent operations in the MRP, the emergency operation technologies for sudden water pollution accidents were developed. This book introduces these emergency operation technologies, including simulation technology for hydrodynamic and water quality in the main canal, traceability technology, emergency operations, and an emergency management system for sudden water pollution accidents.This book is supported by the Major Science and Technology Program for Water Pollution Control and Treatment (2017ZX07108-001) and National Key R&D Program of China (2017YFC0406004).